Green Products and Shariah-Compliant Firms in Indonesia & Malaysia: The Role of Board Gender Diversity - Ishak; Fresinta, Frifalia Fresinta (Global Review of Islamic Economics and Business, 2024)
The issue of sustainable development is one of the most critical issues globally, covering almost all human activities. The design of sustainable development was developed by the United Nations (UN) in 2015, and 17 goals are targeted to be achieved by 2030. If grouped, the 17 goals are divided into three issues, including environmental, social, and governance issues. This study aims to analyze the effect of green-labeled products on firm performance and risk. It focuses on Shariah-compliant firms by adding a moderation analysis of gender diversity in the firm's board structure. The scope of this study is companies in Indonesia and Malaysia. This study examined 130 companies from various industries from the period 2014-2022, employing a panel data approach. Utilizing Generalized Least Squares (GLS) regression for panel data estimation, the finding indicated that green products positively affect firm performance proxied by ROA and ROE. Furthermore, our findings indicated that green products positively affect ZSCORE, suggesting a lower firm risk. The presence of female board members was observed to have a negative effect on risk. The findings of this study provide new insights into companies' implementation of green products. They are expected to be taken into consideration in decision-making for companies and regulators.